Jean Desmet and the Early Dutch Film Trade - Blom, Ivo (Film Culture in Transition, 2003)
Since 1957 the Film Museum in Amsterdam has been in possession of the Desmet Collection which contains the estate of the Dutch cinema owner and film distributor Jean Desmet (1875-1956). The collection comprises almost nine hundred European and American films in all genres, a collection of publicity material and a dauntingly large business archive. These three sources form the basis of this first comprehensive reconstruction of Desmet's career: from his nomadic beginnings as a traveling showman, working the seasonal fairgrounds of the Netherlands and Belgium, to his successful switch to permanent cinema operation and film distribution. The history of Desmet's career offers not simply an abstract of an individual character and his personal ambitions and motivations, but also epitomizes transformations in the world of cinema as an industry. Between 1907 and 1916 the world of cinema experienced radical structural change which Desmet not only witnessed but also helped to bring about. Given the insufficiencies of Dutch film production, Desmet became a link between film production abroad and film exhibition in the Netherlands. Desmet is not merely representative of the rise of the permanent movie house and the coming of the film distributor. This book shows how his fortunes also encapsulate a series of structural changes within the new culture of permanent cinema and film distribution. In film distribution these changes embraced the introduction of film rental, the advent of the long feature film, the introduction of the monopoly distribution system and the periodic transformation of the products on offer. In the business of cinema operation change involved specialization, the creation of fixed theater venues, the development of a theater hierarchy, expansions of scale, the introduction of trade journals and the gradual legitimization of cinema as a popular cultural institution. These transformations were not confined to the Netherlands but were also taking place in the rest of Europe. Indeed, they were first set in motion by other European countries, and in order fully to understand Desmet it is necessary to situate him in his larger European context. In this original and wide-ranging study Ivo Blom uses the career of Jean Desmet as a means of exploring the history of cinema from the ground-level position of film distribution and exhibition. His copiously illustrated and scrupulously documented exposition swells into an epic narrative that offers a richer, more rounded -indeed 'truer' - account of early urban cinema culture than is possible from the confined perspective of production-based film histories.